2021
DOI: 10.1002/smll.202100629
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Understanding the Electrocatalytic Reconstruction Chemistry of Coordination Compounds

Abstract: Coordination compounds including mainstream metal‐organic frameworks and Prussian blue analogues receive extensive researches when they directly serve as electrocatalysts. Their reconstruction phenomena, that are closely associated with actual contributions and intrinsic catalytic mechanisms, are expected to be well summarized. Here, the recent advances in understanding reconstruction chemistry of coordination compounds are reviewed, including their main classifications and structural properties, reconstructio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 209 publications
(230 reference statements)
0
10
0
Order By: Relevance
“…We kindly refer readers to recent representative reviews and research publications. 28,29,262,285,393,395,680 The combination of the obtained time-resolved information (sections 4.2 and 4.3) with those mentioned design principles (section 6.1.1) will contribute to the development of efficient and robust OER catalysts and pave the way to a carbon-neutral society.…”
Section: ) Leaves the Following Question Open: Do The Oxidized Anioni...mentioning
confidence: 99%
“…We kindly refer readers to recent representative reviews and research publications. 28,29,262,285,393,395,680 The combination of the obtained time-resolved information (sections 4.2 and 4.3) with those mentioned design principles (section 6.1.1) will contribute to the development of efficient and robust OER catalysts and pave the way to a carbon-neutral society.…”
Section: ) Leaves the Following Question Open: Do The Oxidized Anioni...mentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) with structural diversity, tunability and functionality have been utilized in varied fields including electrochemical energy conversion. The electrochemical conversion mainly depends on redox-active metal nodes, redox-active linkers, and/or host–guest redox activation . Particularly, in the field of electrochemical CO 2 reduction reaction (CO 2 RR), MOFs exhibit unique advantages not only because of their well dispersed metal centers with redox activity for CO 2 electroreduction, but also owing to their tunable porosity to enhance adsorption of CO 2 making electron transfer easier from active site to CO 2 molecules. , Moreover, MOFs with atomically dispersed metal sites provide a potential platform for design and application of single-site catalysts. For example, two-dimensional (2D) Cu-MOF with copper nodes as single active sites realized CO 2 RR to give CO through the fast reversible change between Cu 2+ and Cu + .…”
Section: Introductionmentioning
confidence: 99%
“…The first studies of MOFs considered them true catalysts for the OER . However, similar to many molecular systems, the degradation or removal of organic fragments causes the decomposition of the molecular catalysts to metal (hydr)­oxides after the OER. , On the other hand, metal (hydr)­oxides (Mn, Fe, Co, Ni, and Cu) are efficient catalysts for the OER. Among different metal (hydr)­oxides, Ni–Fe layered double hydroxide (LDH) are efficient OER catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, the study by Zhang’s group indicated that Ni–Fe Prussian blue analogue transformed to an Fe–Ni layered double hydroxide during the OER . Recently, the conversion of MOFs to metal (hydr)­oxides under the OER was investigated by some research groups. Although previous studies have pointed to the conversion of some MOFs to metal (hydr)­oxides, the details of this conversion are unknown.…”
Section: Introductionmentioning
confidence: 99%